Judging guilt and accuracy: highly confident eyewitnesses are discounted when they provide featural justifications - Dodson, Chad S. (Psychology, crime & law, 2017)
Jurors are heavily swayed by confident eyewitnesses. Are they also influenced by how eyewitnesses justify their level of confidence? Here we document a counter-intuitive effect: when eyewitnesses identified a suspect from a lineup with absolute certainty (‘I am completely confident’) and justified their confidence by referring to a visible feature of the accused (‘I remember his nose’), participants judged the suspect as less likely to be guilty than when eyewitnesses identified a suspect with absolute certainty but offered an unobservable justification (‘I would never forget him’) or no justification at all. Moreover, people perceive an eyewitness’s identification as nearly 25% less accurate when the eyewitness has provided a featural justification than an unobservable justification or simply no justification. Even when an eyewitness’s level of confidence is clear because s/he has expressed it numerically (e.g. ‘I am 100% certain’) participants perceive eyewitnesses as not credible (i.e. inaccurate) when the eyewitness has provided a featural justification. However, the effect of featural justifications - relative to a confidence statement only - is maximal when there is an accompanying lineup of faces, moderate when there is a single face and minimal when there is no face at all. The results support our Perceived-Diagnosticity account.